Dietary intervention for people with mental illness in South Australia. (26th July 2016) - Bogomolova, Svetlana; Zarnowiecki, Dorota; Wilson, Amy; Fielder, Andrea; Procter, Nicholas; Itsiopoulos, Catherine; O'Dea, Kerin; Strachan, John; Ballestrin, Matt; Champion, Andrew; Parletta, Natalie
Abstract: Background: People with serious mental illness (SMI) have a 25–30 year lower life expectancy than the general population due largely to cardiovascular disease (CVD). Mediterranean diet can reduce CVD risk and repeat events by 30–70%. We conducted a pilot feasibility study (HELFIMED) with people who have SMI residing within a Community Rehabilitation Centre in South Australia, aimed at improving participants' diets according to Mediterranean diet principles. Methods: During a 3-month intervention, participants were provided with nutrition education, food hampers, and twice-weekly cooking workshops and guided shopping trips. This report presents the results of a mixed method evaluation of the programme using thorough in-depth interviews with participants and support staff ( n  = 20), contextualized by changes in dietary biomarkers and CVD risk factors. Results: The framework thematic analysis revealed evidence of improvements in participants' knowledge of and intake of the key elements of a Mediterranean-style diet (fruit and vegetables, olive oil, fish, legumes), reduction in poor nutrition habits (soft drinks, energy drinks, take away meals) and development of independent living skills—culinary skills such as food preparation and cooking based on simple recipes, food shopping and budgeting, healthy meal planning and social interaction. These changes were supported by dietary biomarkers, and were associated with reduced CVD risk factors. Conclusions: A Mediterranean diet-based pilot study achieved positive change in dietary behaviours associated with CVD risk for participants with SMI. This supports a need to include dietary education and cooking skills into rehabilitation programmes for people with SMI.